The Development and standardization of speech test material in English for Indians - KC, Swarnalatha (Journal of All India Institute of Speech and Hearing, 1972)
Speech audiometry is an important element in the battery of audiometric tests. Speech tests need to be standardized on the population to be tested. Speech tests in Indian languages are at present being made up. However, as an interim measure the standardized tests in English are used with English-knowing Indians. However pilot studies (Nikam, 1968) have indicated that the available tests may not be wholly suitable to Indian population because many words in the test are unfamiliar to us and this can affect performance. Here an attempt is to be made to modify the existing speech tests, to suit our conditions. The proposed study is "the development and standardization of speech tests in English for Indian population".